Harnessing the power of marine terpenoids against diabetes-associated oxidative stress - Derren David Christian Homenta Rampengan; Juan Alessandro Jeremis Maruli Nura Lele; Raffaele Romano; Nurpudji Astuti Taslim; Raymond Rubianto Tjandrawinata; Antonello Santini; Fahrul Nurkolis; Fahrul Nurkolis; Fahrul Nurkolis (Frontiers in Nutrition)
Diabetes mellitus (DM), particularly type 2 diabetes (T2DM), remains a significant global health concern, driven largely by oxidative stress-induced damage. Marine terpenoids, bioactive compounds extracted from diverse marine organisms such as algae, sponges, and corals, present promising antioxidant and antidiabetic potential. This review systematically evaluates the chemical diversity, biological sources, and mechanisms of action of marine terpenoids in mitigating diabetes-associated oxidative stress. Marine terpenoids exhibit potent antioxidant capabilities via radical scavenging, modulation of cellular antioxidant defenses, regulation of redox-sensitive pathways such as Nrf2/ARE and NF-κB, metal chelation, and pro-oxidant enzyme inhibition. Preclinical studies underscore their efficacy in reducing hyperglycemia, enhancing insulin sensitivity, preserving pancreatic β-cell function, and protecting against diabetic complications, including nephropathy and cardiovascular diseases. Despite the promising preliminary results, further studies addressing bioavailability, pharmacokinetics, long-term safety, and sustainability are imperative to establish marine terpenoids as viable therapeutic options for diabetes management.